1995
DOI: 10.1073/pnas.92.17.8074
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor rapidly enhances synaptic transmission in hippocampal neurons via postsynaptic tyrosine kinase receptors.

Abstract: Although neurotrophins are primarily associated with long-term effects on neuronal survival and differentiation, recent studies have shown that acute changes in synaptic transmission can also be produced. In the hippocampus, an area critically involved in learning and memory, we have found that brain-derived neurotrophic factor (BDNF) rapidly enhanced synaptic efficacy through a previously unreported mechanism-increased postsynaptic responsiveness via a phosphorylation-dependent pathway. Within minutes of BDNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
380
1
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(406 citation statements)
references
References 35 publications
22
380
1
3
Order By: Relevance
“…For the time-course analysis, a response was defined as a sustained increase in activity at least 2 SEs over baseline. Consistent with our previous work (Levine et al, 1995), the majority of recorded neurons under control conditions responded to depolarization of Ϫ40 mV with an increase in mEPSC frequency. The small number of cells that did not respond were assumed to be of a different neuronal subtype and were not included in the analysis.…”
Section: Event Criteriasupporting
confidence: 79%
“…For the time-course analysis, a response was defined as a sustained increase in activity at least 2 SEs over baseline. Consistent with our previous work (Levine et al, 1995), the majority of recorded neurons under control conditions responded to depolarization of Ϫ40 mV with an increase in mEPSC frequency. The small number of cells that did not respond were assumed to be of a different neuronal subtype and were not included in the analysis.…”
Section: Event Criteriasupporting
confidence: 79%
“…Thus the measured effects that we report here were long-term and not acute, as previously studied in BDNF (Brunig et al 2001;Frerking et al 1998;Kang and Schuman 1995;Kim et al 1994;Levine et al 1995;Li et al 1998;Tanaka et al 1997) or NT-3 (Kang and Schuman 1995;Kim et al 1994).…”
Section: Measurement Of Neural Activity Propagationsupporting
confidence: 51%
“…Using cultured hippocampal neurons as a model system, BDNF has been shown to enhance transmitter release via a mechanism inhibitable by expression of a dominant negative variant of TrkB in presynaptic cells (Li et al, 1998), suggesting a presynaptic locus via the receptor TrkB. In contrast, BDNF has been shown by different groups to enhance not only presynaptic transmitter release but also postsynaptic transmission through NMDA channels in cultured hippocampal neurons (Levine et al, 1995(Levine et al, , 1998. Interneurons are also a potential locus for BDNF action, because BDNF deficiency clearly inhibits the differentiation of these neurons (Jones et al, 1994), and acute application of BDNF has been shown to decrease inhibition in slices from adult animals (Tanaka et al, 1997;Frerking et al, 1998).…”
Section: Abstract: Trkb; Conditional Mutant; Ca1; Long-term Potentiamentioning
confidence: 99%